ERROR ANALYSIS IN TRANSLATING INDEFINITE ARTICLE ON MODIFIED AND NON-MODIFIED NOUN - Arni Arsyad Sultan (International Journal of Research on English Teaching and Applied Linguistics, 2022)
Indefinite article in the surface may seem unimportant but it has uniqueness. Indefinite article “a” or “an” in a noun phrase can differentiate the number of noun without using plural mark. Besides, it cannot be used with certain nouns. Regarding this rule, it should be easy because there is a clear border. However, students of this research still could not acknowledge the rule of use of indefinite article. In another word, the goal of this research is to reveal the translation of indefinite article followed by noun or noun phrase and the classification of errors they make. The respondents are the fifth semester students of English Education Department in IAIN Bone.  The sample of this research is 20 students from English education department who have been taught the material of article as registered in 2019/2020 academic year. The sentences translated by respondents are retrieved from book A Practical English Grammar (Thomson Martinet, 1986) and from website https://www.vedantu.com/english/omission-of-article. Sentences are shared through Whatsapp text as well as the answers from the students. The data are analyzed by using descriptive qualitative method. The result of this research is that students still make error in translating the noun phrase in which they are still not able to differentiate the translation of noun or noun phrase with article or they should omit it.